MEMBANGUN SISTEM KINERJA MELALUI KEMAMPUAN KERJA DAN MOTIVASI PADA PERUSAHAAN PERKAPALAN - Recky, Recky; Gurawan Dayona Ismail; Nazaruddin_Nazaruddin; Sofiandi_Sofiandi (Indragiri Research Center (ingreat), 2023)
This research was conducted at Shipping Companies in the Riau Islands Region with the aim of knowing the employee performance system and work ability and motivation in workers. The research population conducted by researchers was employees at 3 shipping companies using a sampling method, namely accedental sampling of 71 employees. The analytical tool used to measure research using the Structural Equational Model processed with SmartPLS software. The results of the analysis prove that there is a significant effect of work ability on employee performance, there is a significant effect of motivation on employee performance, there is a significant effect of work ability on employee performance and work motivation acts as a mediating variable on the effect of work ability on employee performance.